Feedback and uptake in videoconferences for online intercultural exchange - Ruiling Feng; Xiuhong Shi; Songlian Hu; Yong Yu (University of Groningen Press, 2021)
Incidental focus on form (FonF) refers to the treatment of linguistic elements incidentally arising in a communicative setting during a meaning-focused activity. Videoconferencing for Online Intercultural Exchange (OIE) projects represents a typical meaning-focused communication activity but incidental FonF in group-based OIE projects is underexplored. The present study investigated the longitudinal changes of feedback types and factors related to successful uptake in Zoom-based videoconferences during a five-week OIE project. Chinese students and US students participated in weekly Zoom videoconferences to collect intercultural student ethnography data for their group projects with English as the exchange language. The videoconferences were recorded, transcribed, coded, and subsequently analysed quantitatively. Results returned that recast, clarification request, and translation were more frequently used but their frequencies did not significantly fluctuate throughout the OIE project, while metalinguistic feedback, elicitation, and explicit corrective feedback were less commonly used but their frequencies of use varied significantly. Repair provider (self-repair vs. other repair) and English proficiency were significantly associated with Chinese students' successful uptake. The findings have implications for incorporating OIE and similar virtual exchange models into language teaching and learning.